Microwave absorption properties of Fe2O3 and Fe2O3/CNTs nanocomposites - Azis, Raba'ah Syahidah; Shaari, Abdul Halim; Awang Kechik, Mohd Mustafa; Lim, Kean Pah; Chen, Soo Kien; Muhammad, Farah Diana; Matori, Khamirul Amin; Ismail, Ismayadi; Elmahaishi, Madiha Fathi (The Malaysian Solid-State Science and Technology Society, 2024)
The dielectric loss properties of recycled Fe2O3 (iron oxide nanoparticles, hematite) can be enhanced by using it as a catalyst for synthesizing carbon nanotubes (CNTs) from waste cooking oil. Hematite was successfully processed using the high-energy ball milling (HEBM) method for 12 h and sintered at 600 °C for 4 h. This work aimed to improve the electromagnetic (EM) wave absorption characteristics in the frequency range of 8−18 GHz by increasing interfacial polarization and dielectric loss resulting from the growth of CNTs. Our results indicated that Fe2O3/CNTs showed the highest microwave absorption, exceeding 99.9%, with a minimum reflection loss of –15.05 dB and an absorption bandwidth of 1.68 GHz. The microwave absorption properties of these nanocomposites were attributed to the combined effects of dielectric loss from CNTs and magnetic loss from hematite.